Biochar interventions enriched with alginate-producing bacteria support the growth of maize in degraded soils. Issue 1 (April 2020) - Sukmawati,; Ala, A; Baharuddin,; Gusli, S
Abstract: Biochar enriched with alginate-producing bacteria increases the ability of the soil to retain air so that it is available for the growth and production of maize in dry land. Pot experiments with mixed clay media with three types of biochar from oil palm shells, oil palm empty fruit bunches and corncob were conducted to study the interaction of biochar and alginate-producing bacteria (alginate production, phosphate solvent and nitrogen fixation) water (100%, 80% and 60%) on the growth of corn plants. Experimental results prove biochar factors, alginate-producing bacterial isolates and field capacity differ significantly from the vegetative phase of corn. Biochar interaction of corncobs with water at 100% lands capacity produces the best crops, but produces leaf area at 80% field capacity. While the interaction of corncob biochar with N-binding bacterial isolates produced the highest number of leaves. Correlation between variables that use role, biochar on the efficiency of water use for maize growth, where plant height, leaf number, leaf number and dry weight are negatively correlated with KAKL. This study provides the latest synthesis to discuss the use of biochar and bacteria as a strategy to increase support for food production of dry land that increases degradation.